B Peningkatan Kualitas Pengetahuan Tentang Resiko Hipertensi Pada Ibu Hamil Desa Aek Haruaya Kabupaten Padang Lawas Utara - Harahap, Riska Yanti; Sundari, Dewi Wulan; Zelly Okta Taren (JURNAL SUAKA INSAN MENGABDI (JSIM), 2024)
Hypertension is an increment in systolic and diastolic blood weight over typicallevels. In Indonesia, the predominance of hypertension based on estimationcomes about within the youthful to elderly populace is 34.1% to 55.2%.Variables that cause hypertension comprise of essential hypertension andauxiliary hypertension. This investigate points to decide the hazard variables forhypertension that happen within the community in Aek Haruaya Town, NorthPadang Lawas Rule, Portibi Locale in 2024. The sort of inquire about utilized isquantitative using descriptive expository strategies for pregnant ladies andemploying a cross sectional approach. Taking Respondents Utilizing PurposiveTesting Method, 64 Respondents Age Extend 18 A long time and Over. FactualTests in Analyzing This Investigate Data Use the Chi-Square Strategy. Thecomes about of this ponder appear that there's a relationship between pregnantladies, age (P-Value=0.005), smoking history (P-Value=0.014), and Body MassList (BMI) (P-Value=0.004) with the rate of hypertension in pregnant ladies. InAek Haruaya Town, North Padang Lawas Rule, Portibi Locale in 2024. It istrusted that individuals can halt smoking and decrease their body mass, so thatindividuals can decrease the frequency of hypertension and make strides the levelof open wellbeing.